A Modified Hyaluronic Acid–Based Dissolving Microneedle Loaded With Daphnetin Improved the Treatment of Psoriasis - Peng, Shiya; Cheng, Liuhanghang; Wu, Qian; Li, Yuanchao; Ran, Lei; Wang, Wei; Huang, Ke; Zhu, Rong; Xue, Sihong; Zhou, Chunli; Zhu, Weidong; Cheng, Biao; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Psoriasis is a common chronic immune-inflammatory disease. Challenges exist in the present treatment of psoriasis, such as difficulties in transdermal drug administration and severe side effects. We hope to achieve a better therapeutic outcome for psoriasis treatment. By using modified soluble microneedles (MNs) loaded with daphnetin, the psoriasis symptoms of mice, the abnormal proliferation of keratinocytes, and the secretion of inflammatory factors were significantly reduced. In vitro, daphnetin is proven to inhibit the NF-κB signaling pathway and to inhibit the proliferation of HaCaT cells and the release of inflammatory factors, especially CCL20. This research showed that the modified microneedle loaded with daphnetin optimized transdermal drug delivery and relieved the symptoms of psoriasis more effectively. The novel route of Daph administration provides a future research direction for the treatment of psoriasis.